Afghan Rugs Pattern in a Visual Ethnographic Perspective - Shaheera Barmaki (ASSOCIATION FOR SCIENTIFIC COMPUTING ELECTRICAL AND ENGINEERING (ASCEE), 2020)
Carpets are the most important and most famous handicraft item from Afghanistan. There are various patterns of carpet weaving in the provinces of North and Northwest Afghanistan. The development of carpet patterns in Afghanistan is very dynamic. In the past, traditional carpets contained stories, beliefs, and prayers. These patterns have adapted to the social, political, and cultural conditions of the Afghan people. This has led to a change in the Afghan carpet pattern. The problem is how the pattern changes occur, what is behind the changes. This research intends to reveal this problem. The method used is qualitative—data obtained from collecting visual data from carpet artisans. Data grouping consists of traditional and modern visual carpet data, and then the data is analyzed using a visual ethnographic approach. The assumptions made in this study are that the patterns and designs of Afghan rugs that started before the alphabet, until the Afghan war conflict or until now, are caused by the craftsmen's closeness to the problems they face and their life trends, which are influenced by the socio-political conditions of the country. The duration of the war in Afghanistan has affected many things, including the design of the carpet pattern. It can be seen that the patterns of soldiers, helicopters, and weapons are found in the creation of the carpet. This study concludes that this change in pattern occurs due to psychological pressures caused by war. The massive displacement of the Afghan population outside the country, and in the country where they come, has the effect of forming a new pattern. The way a carpet engraver makes a pattern change is by creating a pattern unit, repeating the design, and cultivating the pattern organization system. The changes were made as a result of the interpretation process carried out by Afghan carpet craftsmen